1997
DOI: 10.1016/s0735-1097(97)00114-9
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Atrioventricular Node Reciprocating Tachycardia Masquerading as Tachycardia Using a Left-Sided Accessory Pathway

Abstract: Atypical AVNRT with eccentric retrograde left-sided activation was demonstrated in 6% of all patients with AVNRT masquerading as tachycardia using a left-sided accessory pathway. Ablation of the slow pathway at the posterior aspects of the right atrial septum resulted in a cure in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 31 publications
3
90
2
Order By: Relevance
“…[5][6][7] In some cases with such connection, especially to the left atrium, it is likely that atypical AVNRT is induced by eccentric retrograde left-sided activation. 8,10,14) In the present electrophysiologic study, double observations of the jump-up phenomenon suggest that triple AV nodal pathways are present. About the retrograde left-sided activation, long and decremental conduction negates the participation of the accessory pathway recognized in concealed WPW syndrome.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…[5][6][7] In some cases with such connection, especially to the left atrium, it is likely that atypical AVNRT is induced by eccentric retrograde left-sided activation. 8,10,14) In the present electrophysiologic study, double observations of the jump-up phenomenon suggest that triple AV nodal pathways are present. About the retrograde left-sided activation, long and decremental conduction negates the participation of the accessory pathway recognized in concealed WPW syndrome.…”
Section: Discussionsupporting
confidence: 48%
“…[5][6][7] Hwang, et al have reported that AVNRT with left-sided activation, which may occur with such a connection, is relatively rare. 8) In this report, we describe a patient with AVNRT caused by a left-sided pathway that was confirmed by the success of radiofrequency catheter ablation.…”
mentioning
confidence: 67%
See 3 more Smart Citations